1996
DOI: 10.1128/mcb.16.10.5634
|View full text |Cite
|
Sign up to set email alerts
|

NF-E2 Disrupts Chromatin Structure at Human β-Globin Locus Control Region Hypersensitive Site 2 In Vitro

Abstract: The human beta-globin locus control region (LCR) is responsible for forming an active chromatin structure extending over the 100-kb locus, allowing expression of the beta-globin gene family. The LCR consists of four erythroid-cell-specific DNase I hypersensitive sites (HS1 to -4). DNase I hypersensitive sites are thought to represent nucleosome-free regions of DNA which are bound by trans-acting factors. Of the four hypersensitive sites only HS2 acts as a transcriptional enhancer. In this study, we examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 63 publications
6
74
0
Order By: Relevance
“…At sites where GATA-1 binding does not require FOG-1, such as HS3, neighboring proteins might provide an activity to render the local chromatin configuration permissive to GATA-1 binding. For example, previous studies have shown that GATA-1 binding to chromatinized templates in vitro is facilitated by prior binding and recruitment of remodeling activity by the transcription factor NF-E2 (44).…”
Section: Hs2 (mentioning
confidence: 99%
“…At sites where GATA-1 binding does not require FOG-1, such as HS3, neighboring proteins might provide an activity to render the local chromatin configuration permissive to GATA-1 binding. For example, previous studies have shown that GATA-1 binding to chromatinized templates in vitro is facilitated by prior binding and recruitment of remodeling activity by the transcription factor NF-E2 (44).…”
Section: Hs2 (mentioning
confidence: 99%
“…NURF activity is abundant in chromatin reconstitution extracts derived from Drosophila embryos (91,92) that are increasingly employed for analyses of the activities of sequencespecific transcription factors in a native chromatin context (87,(93)(94)(95)(96)(97). In these crude extracts, a number of transcription factors (GAGA factor, HSF, GAL4, Sp1, NF-B, NF-E2, and lac repressor) have been reported to participate in nucleosome disordering and, in several cases, to stimulate transcription manyfold on chromatinized templates.…”
Section: Atp-dependent Nucleosome Remodeling Factorsmentioning
confidence: 99%
“…However, deletion of the LCR DNA sequences severely reduces the transcription of the ␤-like genes, but the DNase hypersensitivity and polymerase II association with promoters of the remaining ␤-globin genes persists (17)(18)(19). Several biochemical studies in cell lines suggest that the MARE sequences of HS2, apart from their involvement in the enhancement of transcription, also take part in the alteration of the chromatin structure of HS2 and a linked promoter (20)(21)(22)(23). These studies suggest the possible association of the LCR with specific chromatin remodeling activities, although such a LCR-specific chromatin remodeling activity has not been isolated.…”
mentioning
confidence: 99%